Composition
A balanced composition of acrylic monomers, elastomers, organic peroxide, and cobalt compounds in SGAs enhances metal adhesion and curing speed, providing extended pot life and strong adhesion, overcoming the limitations of conventional SGA technologies.
Patent Information
- Application Number
- JP2024195394
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional second-generation acrylic adhesive compositions (SGAs) face challenges in achieving a balance between metal adhesion and curing speed, with issues related to storage stability and insufficient pot life, as well as complex usage requirements.
A composition comprising (meta) acrylic monomers, elastomers with a carbon-carbon double bond structure, organic peroxide, and organic compounds containing cobalt, formulated to provide a pot life exceeding 100 minutes and excellent metal adhesion, with a balanced ratio of components ensuring effective adhesion and curing.
The composition achieves a prolonged pot life, excellent adhesion to metals like iron and aluminum, with tensile shear strengths exceeding 10 MPa after 24 hours, while maintaining non-stickiness on the cured surface, addressing the limitations of previous SGA technologies.
Smart Images

Figure 2025013588000001 
Figure 2025013588000002 
Figure 2025013588000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition, particularly a curable composition that exhibits long handling time and excellent metal adhesion. [Background technology]
[0002] Second generation acrylic adhesive compositions (SGA), which are two-component acrylic adhesive compositions, are known as adhesives that cure at room temperature. SGAs are generally of the two-component type, consisting of a first component containing an organic peroxide and a second component containing a reducing agent that decomposes the organic peroxide contained in the first component and generates radicals, with both the first and second components containing main components such as polymerizable (meth)acrylic monomers and elastomers.
[0003] The two-part SGA has the following features: excellent adhesiveness can be achieved without precisely mixing the first and second parts, and adhesion to oily surfaces is possible. Various proposals have been made regarding such SGA, as described in Patent Documents 1 to 5. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-160861 A [Patent Document 2] JP 2008-156426 A [Patent Document 3] JP 2017-206574 A [Patent Document 4] JP 2017-075279 A [Patent Document 5] Japanese Patent Application Publication No. 06-080937 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the SGA according to the conventional technology could not solve the problem of a trade-off between metal adhesion and hardening speed. For example, Patent Document 1 discloses a composition capable of bonding metals to porous materials such as concrete, paper, or cloth, which contains a (meth)acrylic acid ester monomer, cobalt soap, and a nitrogen-containing compound. This composition exhibits adhesion to porous materials due to the action of cobalt ions. However, in light of the current standards required with technological development, it is believed that there is still room for improvement in the metal adhesion according to the conventional technology.
[0006] Patent Document 2 discloses an adhesive composition containing a polymerizable vinyl monomer, a curing agent, a thiourea derivative, and an elastomer component, and having oily surface adhesion. The adhesive strength of this composition depends on the polymerization reaction of the thiourea derivative. Therefore, in light of the currently required level, this conventional technology is considered to have room for improvement in terms of achieving both pot life and adhesive strength.
[0007] Patent Documents 3 and 4 disclose a two-component adhesive that contains an elastomer such as chlorosulfonated polyethylene, a polymerizable monomer having a (meth)acryloyl group, an organic peroxide, a nitrile butadiene rubber, an amine-based activator, and a copper-based compound or an organometallic compound. However, this adhesive obtains its adhesive strength through the action of an amine-based activator such as toluidine, which is a curing accelerator, and therefore cannot solve the problem of poor storage stability. In addition, in light of the currently required level, the pot life is not long enough, and even if the pot life is extended, the adhesive strength decreases.
[0008] Patent Document 5 discloses a base-primer type acrylic adhesive consisting of a base mainly composed of a polymerizable (meth)acrylic monomer and an organic peroxide, and a primer mainly composed of a reducing agent that forms a redox catalyst system with the organic peroxide in the base, the primer mainly composed of an aldehyde and amine condensate and a soluble vanadium compound, and at least one of the base or primer contains one or more acidic compounds selected from acidic phosphorus compounds, organic carboxylic acids, and organic sulfonic acids. However, this adhesive also does not solve the problem of insufficient pot life in light of the current standards, and requires a primer, which makes the method of use complicated. [Means for solving the problem]
[0009] The present inventors have arrived at the present invention, which can solve the above problems. That is, the present invention can provide the following aspects.
[0010] Aspect 1. (1) a (meth)acrylic monomer; (2) an elastomer having no (meth)acrylic groups and having a carbon-carbon double bond structure in a ratio of 10% to 90%; (3) an organic peroxide; (4) Organic compounds containing cobalt A composition comprising: The amount of component (2) is 20 parts by mass or less per 100 parts by mass of the total of components (1) and (2), (4) The number of carbon atoms in one molecule of the component is 12 to 19. A composition comprising:
[0011] Aspect 2. (2) The composition according to embodiment 1, wherein the carbon-carbon double bond structure of the component contains a butadiene structure.
[0012] Aspect 3. The composition of any one of the preceding aspects, wherein the (4) component comprises cobalt 2-ethylhexanoate.
[0013] Aspect 4. The composition according to any one of Aspects 1 to 3, characterized in that it has a pot life of 100 minutes or more as measured by Method 5 "Determination by exothermic reaction temperature" as specified in JIS K 6870:2008, a tensile shear adhesive strength after 24 hours to iron-iron bond of 10 MPa or more as measured by the method specified in JIS K 6850:1999 and a cohesive failure is observed as a failure state, and the surface of the cured product is non-tacky as measured by the Ballochny method as specified in JIS K 5600-3-2:1999.
[0014] Aspect 5. The composition according to any one of Aspects 1 to 4, which is a two-part type composition, in which a first part contains at least (3) an organic peroxide, and a second part contains at least (4) an organic compound containing cobalt.
[0015] Aspect 6. An adhesive composition comprising the composition according to any one of the first to fifth aspects.
[0016] Aspect 7. A bonded body obtained by bonding adherends with the adhesive composition according to embodiment 6.
[0017] Aspect 8. A bonding method comprising bonding adherends using the adhesive composition according to embodiment 6. Effect of the Invention
[0018] The composition provided by the embodiment of the present invention has the effect of ensuring sufficient pot life (also called open time), while also providing excellent adhesion and metal adhesion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to these embodiments. In this specification, "parts" and "%" are based on mass unless otherwise specified. Numerical ranges in this specification include upper and lower limits unless otherwise specified. In this specification, the "amount used" and "content" of a component refer to the amount based on the entire composition unless otherwise specified.
[0020] In this specification, the term "monofunctional (meth)acrylate" refers to a (meth)acrylate having one (meth)acryloyl group (sometimes referred to as a (meth)acrylic group) in the present specification. In addition, the term "polyfunctional (meth)acrylate" refers to a (meth)acrylate having two or more (meth)acryloyl groups.
[0021] A preferred composition for providing an embodiment of the present invention is a curable composition. The curable composition (hereinafter, sometimes simply referred to as "composition") contains (1) a (meth)acrylic monomer, (2) an elastomer having no (meth)acrylic group and having a carbon-carbon double bond structure in a ratio of 10% to 90%, (3) an organic peroxide, and (4) an organic compound containing cobalt.
[0022] (1) (meth)acrylic monomer has a function of dissolving other components of the composition. Component (1) is preferably one or more monomers selected from (meth)acrylates and hydroxyalkyl (meth)acrylates having a hydrocarbon group. Such a hydrocarbon group is preferably an unsubstituted or substituted hydrocarbon group having 1 to 32 carbon atoms. The hydrocarbon group may be a linear, branched, or alicyclic aliphatic group, an aromatic group, or a combination thereof. From the viewpoint of obtaining sufficient solubility of other components, component (1) preferably contains one or more (meth)acrylates or hydroxyalkyl (meth)acrylates having an aliphatic group.
[0023] Component (1) may be a monofunctional (meth)acrylate, a polyfunctional (meth)acrylate, or a mixture thereof.
[0024] Examples of the (1) component having a linear or branched aliphatic group and being monofunctional include alkyl (meth)acrylates and hydroxyalkyl (meth)acrylates, etc. Further examples of monofunctional (meth)acrylates include 2-hydroxyethyl (meth)acryloyl phosphate, 4-butylhydroxy (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, glycerin di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, and caprolactone-modified 2-hydroxyethyl (meth)acrylate.
[0025] The alkyl (meth)acrylate is preferably a (meth)acrylate represented by the following formula (1). Formula (1) Z1-OR 11 (Wherein, Z1 represents a (meth)acryloyl group, R 11 represents an alkyl group.)
[0026] Examples of the (meth)acrylate represented by formula (1) include methyl (meth)acrylate, ethyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate (including 2-ethylhexyl (meth)acrylate), nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, dodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicodecyl (meth)acrylate.
[0027] R 11 R represents an alkyl group. 11 is preferably an alkyl group having 1 to 20 carbon atoms, and more preferably an alkyl group having 1 to 10 carbon atoms.
[0028] The alkyl group of the alkyl (meth)acrylate is preferably an alkyl group that is unsubstituted, is not alicyclic, does not have an aromatic group, and does not have a substituent.
[0029] Among the alkyl (meth)acrylates, it is preferable to use methyl (meth)acrylate and octyl (meth)acrylate in combination. When methyl (meth)acrylate and octyl (meth)acrylate are used in combination, the composition ratio by mass of methyl (meth)acrylate:octyl (meth)acrylate is preferably 50-99:1-50, more preferably 60-90:10-40, and most preferably 70-80:20-30.
[0030] The hydroxyalkyl (meth)acrylate is preferably a (meth)acrylate represented by the following formula (2). Formula (2) Z2-O-(R 12 O) p -H (Wherein, Z2 represents a (meth)acryloyl group, R 12 represents an alkylene group, and p represents an integer of 1 to 10.
[0031] Examples of the (meth)acrylate represented by formula (2) include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate.
[0032] R 12 R represents an alkylene group. 12 is -C2H4-, -C3H6-, -CH2CH(CH3)-, -C4H8- or -C6H 12p is preferably an integer of 1 to 10, and more preferably an integer of 1 to 4.
[0033] The hydroxyalkyl group of the hydroxyalkyl (meth)acrylate is preferably a hydroxyalkyl group that is unsubstituted, is not alicyclic, has no aromatic group, and has no substituents other than the hydroxy group.
[0034] Among monofunctional (meth)acrylates, it is preferable to use an alkyl (meth)acrylate and a hydroxyalkyl (meth)acrylate in combination. When an alkyl (meth)acrylate and a hydroxyalkyl (meth)acrylate are used in combination, the composition ratio by mass of the alkyl (meth)acrylate:hydroxyalkyl (meth)acrylate is preferably 1-99:1-99, more preferably 50-95:5-50, and most preferably 70-90:10-30.
[0035] Among the components (1), a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate may be used in combination. When a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate are used in combination, the composition ratio by mass of the monofunctional (meth)acrylate:polyfunctional (meth)acrylate is preferably 50-99:1-50, more preferably 70-90:10-30, and most preferably 75-85:15-25.
[0036] Examples of monofunctional (meth)acrylates having an alicyclic aliphatic group or an aromatic group include adamantyl (meth)acrylate, dicyclopentenyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, 1-(1-adamantyl)-1-methylethyl (meth)acrylate, benzyl (meth)acrylate, methylbenzyl (meth)acrylate, ethylbenzyl (meth)acrylate, propylbenzyl (meth)acrylate, and methoxy. Examples of the acrylates include benzyl (meth)acrylate, chlorobenzyl (meth)acrylate, 2,2-bis(4-(meth)acryloxyphenyl)propane, 2,2-bis(4-(meth)acryloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloxytetraethoxyphenyl)propane, and 2,2-bis(4-(meth)acryloxypolyethoxyphenyl)propane.
[0037] Examples of the polyfunctional (meth)acrylate include alkyl di(meth)acrylate, alkyl tri(meth)acrylate, or alkyl tetra(meth)acrylate having a linear, branched, or alicyclic aliphatic or aromatic group, and preferably, di(meth)acrylate having a bisphenol A skeleton can be used. Examples of the di(meth)acrylate having a bisphenol A skeleton include (poly)ethoxy-modified bisphenol A di(meth)acrylate and (poly)propoxy-modified bisphenol A di(meth)acrylate, and one or more of these can be used. Among these, (poly)ethoxy-modified bisphenol A di(meth)acrylate is preferred. Among the (poly)ethoxy-modified bisphenol A di(meth)acrylate, the compound shown in the following formula (3) is preferred. In the formula, m+n (i.e., ethoxy equivalent) is preferably 1 to 40, more preferably 3 to 20, most preferably 5 to 15, and even more preferably 10. R in the formula 1 and R 2 may each independently be a hydrogen atom or a CH3 group.
[0038] [ka] (m,n are positive numbers)
[0039] Among the (1) (meth)acrylic monomers, monofunctional (meth)acrylates are preferred from the viewpoint of ensuring pot life. The proportion of the monofunctional (meth)acrylate is preferably 50 parts by mass or more, more preferably 70 parts by mass or more, most preferably 80 parts by mass or more, even more preferably 90 parts by mass or more, and even more preferably 100 parts by mass, per 100 parts by mass of the (1) component.
[0040] Among the (1) (meth)acrylic monomers, polyfunctional (meth)acrylates are preferred from the viewpoint of adhesion. The proportion of the polyfunctional (meth)acrylate is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and most preferably 20 parts by mass or less, in 100 parts by mass of the (1) component. The proportion of the polyfunctional (meth)acrylate is preferably 1 part by mass or more, in 100 parts by mass of the (1) component.
[0041] The amount of component (1) used is preferably 80 parts by mass or more and less than 100 parts by mass, and more preferably 80 parts by mass or more and 99 parts by mass or less, when the total amount of components (1) and (2) is 100 parts by mass. If the amount of component (1) is less than 80 parts by mass, the viscosity of the composition becomes too high, which causes a problem that the composition cannot be produced uniformly. Furthermore, if component (2) is not included, there is a problem that the tensile shear strength cannot be obtained sufficiently.
[0042] (2) The elastomer having no (meth)acrylic groups and having carbon-carbon double bond structures in a ratio of 10% to 90% plays a role in imparting tensile shear strength to the composition. In this specification, the term "elastomer" refers to a polymeric substance having rubber-like elasticity at room temperature, and is preferably one that can be dissolved or dispersed in a polymerizable monomer.
[0043] If the proportion of the carbon-carbon double bond structure in the (2) component is 10% or more, the curability can be improved, and if it is 90% or less, the tensile shear strength and curability can be improved, and sufficient metal adhesion can be obtained. If the proportion of the carbon-carbon double bond structure is more than 90%, the radicals generated in the system are consumed in the oxidation of the double bonds, and it is considered that poor curing occurs on the cured surface of the composition that comes into contact with air and on the interface with the adherend. More preferably, the proportion of the carbon-carbon double bond structure in the (2) component may be 20% or more and 80% or less, and even more preferably 30% or more and 80% or less. The carbon-carbon double bond structure in the (2) component preferably contains a butadiene structure.
[0044] (2) The proportion of carbon-carbon double bond structures in the component can be determined by known techniques, such as Fourier transform infrared spectroscopy (FT-IR) or the iodine value calculation method by titration.
[0045] Component (2) has excellent curability due to the absence of a (meth)acrylic group, because component (2) undergoes phase separation with the (meth)acrylic monomer during the polymerization reaction to form an island structure, which does not inhibit the reaction between the (meth)acrylic monomers themselves.
[0046] Examples of component (2) include various synthetic rubbers such as butadiene polymers, styrene-butadiene rubber (SBR, hereinafter sometimes referred to as high styrene rubber), and nitrile rubber (NBR), natural rubber, and various thermoplastic elastomers. Component (2) preferably contains NBR having a butadiene structure in a ratio of 10% to 90%. One or more of these elastomer components may be used as long as there is no problem with compatibility. Of component (2), nitrile rubber (NBR) is preferred.
[0047] The amount of component (2) used is 20 parts by mass or less when the total amount of components (1) and (2) is 100 parts by mass. If the amount of component (2) exceeds 20 parts by mass, the viscosity of the composition becomes too high, which can cause a problem of making it difficult to produce a uniform composition.
[0048] (3) Organic peroxides (also called peroxides) play a role as thermal radical polymerization initiators with excellent reactivity. Examples of the (3) component include cumene hydroperoxide, paramenthane hydroperoxide, and tertiary butyl hydroperoxide. Among these, cumene hydroperoxide is preferred in terms of reactivity.
[0049] The amount of component (3) used is preferably 0.1 to 20 parts by mass, and more preferably 0.5 to 15 parts by mass, when the total of components (1) and (2) is 100 parts by mass. When the amount of component (3) is 0.1 part by mass or more, the curing speed can be appropriately increased, and when it is 20 parts by mass or less, storage stability can be improved.
[0050] (4) The organic compound containing cobalt functions as a reducing agent. The inventors discovered that by making the number of carbon atoms in one molecule of component (4) 12 to 19, the steric hindrance of the ligands can be reduced while the ligands are not made excessively bulky, allowing the ligands to be tightly bonded to the central metal, cobalt element. This makes it possible to moderately limit the rate of the redox reaction of cobalt, and achieves the remarkable effect of efficiently decomposing organic peroxides.
[0051] Furthermore, it is believed that the above-mentioned effects are only obtained when cobalt is used as the central metal. If other reducing agents (e.g., reducing agents with nickel, manganese, or vanadium as the central metal) are used, the above-mentioned effects cannot be obtained even if the carbon number is within the above-mentioned range. This is because cobalt has the highest electronegativity among the first transition metals that have unpaired shared electron pairs in the 3d electron orbitals.
[0052] (4) Examples of component (4) include, but are not limited to, cobalt octylate (also known as "cobalt(II) bis(2-ethylhexanoate)" or "cobalt 2-ethylhexanoate", the number of carbon atoms in one molecule is 16), salcomine (also known as "N,N'-ethylenebis(salicylideneiminato)cobalt(II)", the number of carbon atoms in one molecule is 16), tris(2,4-pentanedionato)cobalt(III) (also known as "acetylacetonate cobalt(III)", the number of carbon atoms in one molecule is 15), and cyclopentadienyl(dimethyl fumarate)(triethyl phosphite)cobalt(I) (the number of carbon atoms in one molecule is 17).
[0053] The amount of component (4) is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 15 parts by mass, and even more preferably 1 to 5 parts by mass, when the total amount of components (1) and (2) is 100 parts by mass. If the amount of component (4) is within this range, the oxidation-reduction reaction rate of cobalt can be appropriately restricted. More preferably, the amounts of components (3) and (4) can be made equal.
[0054] In some embodiments, the composition may be in a two-part form, the first part containing at least component (3) and the second part containing at least component (4), more preferably.
[0055] The composition according to an embodiment may further contain a monomer or polymer of an acid phosphoxyalkyl (meth)acrylate, the amount of which is preferably 0.1 to 5 parts by mass, more preferably 1 to 3 parts by mass, relative to 100 parts by mass of the total of components (1) and (2). As such an acid phosphoxyalkyl (meth)acrylate, a monomer or polymer of a compound having the following formula (4) is preferred.
[0056] [ka] In the formula, A (when there are more than one, each A is independently) is a hydrogen atom, an alkyl group (preferably a C1-C6 alkyl group, more preferably a methyl group), or an alkylhalo group (preferably a C1-C6 alkylhalo group, more preferably a chloro C1-C6 alkyl group, and even more preferably a chloromethyl group). n is an integer of 1 to 6. k is an integer of 1 or 2. R 1 may be a hydrogen atom or a CH3 group.
[0057] The composition according to an embodiment may further contain paraffins to accelerate the curing of the portion of the composition exposed to air, and the amount of paraffins is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 2 parts by mass, when the total of the components (1) and (2) is 100 parts by mass, in terms of curing property and adhesion. Examples of such paraffins include paraffin, microcrystalline wax, carnauba wax, beeswax, lanolin, spermaceti, ceresin, and candelilla wax. Among these, paraffin is preferred. The melting point of the paraffins is preferably 40 to 100°C.
[0058] The composition according to an embodiment may further contain a polymerization inhibitor to improve storage stability, and the amount of the polymerization inhibitor is preferably 0.001 to 3 parts by mass, more preferably 0.01 to 1 part by mass, when the total of the components (1) and (2) is 100 parts by mass, in terms of storage stability and adhesion. Examples of such polymerization inhibitors include methylhydroquinone, hydroquinone, 2,2-methylene-bis(4-methyl-6-tertiarybutylphenol), catechol, hydroquinone monomethyl ether (methoquinone), monotertiarybutylhydroquinone, 2,5-ditertiarybutylhydroquinone, p-benzoquinone, 2,5-diphenyl-p-benzoquinone, 2,5-ditertiarybutyl-p-benzoquinone, picric acid, citric acid, phenothiazine, tertiarybutylcatechol, 2-butyl-4-hydroxyanisole, and 2,6-ditertiarybutyl-p-cresol.
[0059] In one embodiment, an adhesive composition containing the above composition can be provided. In one embodiment, a bonded body formed by bonding adherends with the adhesive composition, and a bonding method thereof can also be provided. When the adherend is a metal, the adhesive composition exhibits excellent adhesion. When the metal is iron or aluminum, the adhesive composition exhibits even better adhesion.
[0060] In a preferred embodiment, the present composition has a pot life (gelation time) measured by method 5 "measurement by exothermic reaction temperature" specified in JIS K 6870:2008 of preferably 100 minutes or more, more preferably 200 minutes or more, and even more preferably 500 minutes or more. When measuring the pot life, it is preferable that the composition is not uncured. The pot life is preferably 1000 minutes or less, more preferably 800 minutes or less.
[0061] In a preferred embodiment, the composition has a tensile shear adhesive strength of 10 MPa or more, more preferably 15 MPa or more, and most preferably 20 MPa or more after 24 hours when measured by the method specified in JIS K 6850:1999 between iron and aluminum. The tensile shear adhesive strength of 10 MPa or more, more preferably 11 MPa or more, and most preferably 12 MPa or more after 24 hours when measured by the method specified in JIS K 6850:1999 between aluminum and aluminum. Generally, a strong adhesive strength is obtained when cohesive failure occurs, so it is preferable that the failure state is cohesive failure. More preferably, the tensile shear adhesive strength is 10 MPa or more and the failure state is cohesive failure. In this specification, the failure state is determined to be cohesive failure when the proportion of cohesive failure based on the entire adhesive area is 80% or more, and when it is less than 80%, the failure state is determined to be interface failure or surface failure.
[0062] In a certain embodiment, it is particularly preferable that all of the following conditions are satisfied in order to have excellent performance. The pot life, measured by method 5 specified in JIS K 6870:2008, is 100 minutes or more. The tensile shear adhesive strength after 24 hours between steel members measured according to the method specified in JIS K 6850:1999 is 10 MPa or more and the failure state is cohesive failure. The tensile shear adhesive strength after 24 hours between aluminum specimens measured according to the method specified in JIS K 6850:1999 is 10 MPa or more and the failure state is cohesive failure. - Based on the Ballochny method specified in JIS K 5600-3-2:1999, there must be no stickiness after curing for 24 hours at room temperature.
[0063] In this specification, "room temperature" refers to the range defined by JIS Z 8703:1983, that is, 5 to 35°C. EXAMPLES
[0064] The present invention will be described in detail below with reference to examples. Using the following materials, curable compositions were prepared according to the formulations shown in the following table. The amounts of components in the table are shown in parts by mass. Unless otherwise specified, the experiments were carried out in an environment of 23°C and 50% Rh (relative humidity).
[0065] <Materials used> As the (meth)acrylate monomer, the following commercially available products were used as they were. Methyl methacrylate: Acryester M (Mitsubishi Chemical Holdings) 2-Hydroxyethyl methacrylate: HEMA (manufactured by Nippon Shokubai) 2-Ethylhexyl methacrylate: Light Ester EH (Kyoeisha Chemical) Ethoxy 10 mole modified bisphenol A dimethacrylate: M-2101 (manufactured by Miwon Specialty Chemical Co., Ltd., in formula (3), R 1 and R 2 is a CH3 group, and m+n=10.)
[0066] The following commercially available elastomers were used as they were (Bd% is the butadiene content). Acrylonitrile butadiene rubber: JSR N220SH (Bd% = 58.5%) (manufactured by JSR) Acrylonitrile butadiene rubber: JSR N250S (Bd% = 80.5%) (manufactured by JSR) High styrene rubber: JSR 0061 (Bd% = 34%) (manufactured by JSR) Methacrylic modified acrylonitrile butadiene rubber: DN612P (Bd%=73%) (manufactured by ZEON) Polybutadiene modified dimethacrylate: TE-2000 (manufactured by Nippon Soda) Polybutadiene: LBR-305 (Kuraray) Chlorosulfonated polyethylene: TS-340 (Tosoh)
[0067] The organic peroxide used was cumene hydroperoxide: Percumyl H-80 (manufactured by NOF Corp.).
[0068] In addition, the following raw materials were used as they were. 2-Hydroxyethyl methacrylate acid phosphate: JPA-514 (manufactured by Johoku Chemical Industry Co., Ltd., R 1 is a CH3 group, A is a hydrogen atom, n is 1, and k is 1 or 2.) Paraffin wax: Paraffin Wax-145 (made by Nippon Seiro, melting point 63°C) Hydroquinone (Seiko Chemical) Methoquinone: MQ (Kawaguchi Chemical Industry) Cobalt octylate: CO-12E (Tokyo Fine Chemical) Vanadyl acetylacetonate (manufactured by Shinko Chemical Industry Co., Ltd.) Nickel octylate: Nickel octylate (manufactured by Nippon Chemical Industries) Manganese octylate: Nikka octylate manganese (manufactured by Nippon Chemical Industry Co., Ltd.) Cobalt(II) acetylacetone (Tokyo Chemical Industry Co., Ltd.) Cobalt naphthenate (Tokyo Chemical Industry Co., Ltd.) Ethylenethiourea (Tokyo Chemical Industry Co., Ltd.)
[0069] <Formulation> The above raw materials were weighed according to the table below and added to a stainless steel 1 L flask. A stainless steel stirring blade was placed in the flask and the mixture was stirred at 200 rpm for 24 hours using a Three-One motor to obtain a uniform viscous liquid.
[0070] <Evaluation> The samples obtained as described above were evaluated based on the following measurement methods. Note that when performing all evaluations, the components A and B were quickly mixed at a mass ratio of 1:1 until homogeneous.
[0071] Pot life: Measured according to Method 5 of JIS K 6870:2008, and the results are shown in the table below. The unit is minutes.
[0072] Adhesion to iron (1-day tensile shear strength (23°C, iron / iron)): The tensile shear adhesive strength of iron (SPCC-SD, Test Piece Co., Ltd.) was measured after 24 hours using a universal testing machine Instron model 4467 (Instron) according to the method specified in JIS K 6850:1999, and the results are shown in the table below. The unit is MPa.
[0073] Adhesion to aluminum (1-day tensile shear strength (23°C, Al / Al)): The tensile shear adhesive strength of aluminum (AL5052, Test Piece Co., Ltd.) was measured after 24 hours using a universal testing machine Instron model 4467 (Instron) according to the method specified in JIS K 6850:1999, and the results are shown in the table below. The unit is MPa.
[0074] Curability: Curability at room temperature was evaluated by the following method. 2The mixed sample was applied so that the mixture was mixed, and left to stand for 24 hours in an environment of 23°C and 50% Rh. After the aging, the surface dryness of the resulting coating film was evaluated by the Ballochni method specified in JIS K 5600-3-2:1999, and the curing property was judged. When the coating film had a dry surface, it was evaluated as not sticky, and the curing property was sufficient, that is, it was judged as ◯. When the Ballochni could not be removed even by lightly brushing it, it was evaluated as sticky, and the curing property was insufficient, that is, it was judged as ×. When the sample was not cured and remained in a liquid state, it was also judged as having insufficient curing property.
[0075] If all of the following conditions are met, a check mark is entered in the "Judgment" column of the table below. If one or more of the following conditions are not met, a check mark is entered in the "Judgment" column of the table below. The pot life measured by method 5 specified in JIS K 6870:2008 was 100 minutes or more. The tensile shear adhesive strength after 24 hours between steel members measured according to the method specified in JIS K 6850:1999 is 10 MPa or more and the failure state is cohesive failure. The tensile shear adhesive strength after 24 hours between aluminum specimens measured according to the method specified in JIS K 6850:1999 is 10 MPa or more and the failure state is cohesive failure. - Based on the Ballochny method specified in JIS K 5600-3-2:1999, there was no stickiness after curing for 24 hours at room temperature.
[0076] [Table 1]
[0077] [Table 2]
[0078] [Table 3]
Claims
1. (1) a (meth)acrylic monomer; (2) an elastomer having no (meth)acrylic group and having a carbon-carbon double bond structure in a ratio of 10% to 90%; (3) an organic peroxide; (4) Organic compounds containing cobalt A composition comprising: The amount of component (2) is 20 parts by mass or less, based on 100 parts by mass of the total of components (1) and (2), (4) The number of carbon atoms in one molecule of the component is 12 to 19. A composition comprising:
2. The composition according to claim 1, wherein the carbon-carbon double bond structure of the component (2) contains a butadiene structure.
3. The composition according to claim 1 or 2, wherein the component (4) comprises cobalt 2-ethylhexanoate.
4. The composition according to any one of claims 1 to 3, characterized in that it has a pot life of 100 minutes or more as measured by Method 5 "Determination by exothermic reaction temperature" specified in JIS K 6870:2008, a tensile shear adhesive strength after 24 hours between iron and steel as measured by the method specified in JIS K 6850:1999 of 10 MPa or more and a state of failure is cohesive failure, and the surface of the cured product is non-tacky based on the Ballochny method specified in JIS K 5600-3-2:1999.
5. The composition according to any one of claims 1 to 4, which is a two-part type composition, the first part containing at least (3) an organic peroxide, and the second part containing at least (4) an organic compound containing cobalt.
6. An adhesive composition comprising the composition according to any one of claims 1 to 5.
7. A bonded body obtained by bonding adherends with the adhesive composition according to claim 6.
8. A bonding method comprising bonding adherends using the adhesive composition according to claim 6.
Citation Information
Patent Citations
Adhesive and joined body
JP2017075279A
Acrylic adhesive comprising main component and primer component
JP1994080937A
Adhesive composition and conjugate using the same and method for producing adhesive composition
JP2006160861A
Curable composition and adhesive composition
JP2008156426A
Adhesive and joined body
JP2017206574A